2008
DOI: 10.1055/s-2008-1038490
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Mental Stress Biomarkers in Ultramarathon

Abstract: We investigated the possible influence of an exhaustive physical exercise on mental stress biomarkers (serotonin, tryptophan, and beta-endorphin) along with dopamine, noradrenaline and free fatty acids in an ultramarathon race in which 45 km was run on the first day and 90 km on the second. We obtained serum samples at 6 different time points during and after the race from 18 Japanese male runners who completed the marathon. Overall changes of serum serotonin and tryptophan concentrations were statistically si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
(14 reference statements)
0
16
0
Order By: Relevance
“…Strong changes of endocrine and metabolic status during marathon runs are described [78,79]. Hormonal changes can influence pain sensation and show an influence on specific brain functions [167].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strong changes of endocrine and metabolic status during marathon runs are described [78,79]. Hormonal changes can influence pain sensation and show an influence on specific brain functions [167].…”
Section: Discussionmentioning
confidence: 99%
“…Some hypotheses explain this based on the influence of the stress hormone cortisol [70] but further pathophysiological principles leading to this decrease in brain volume are not understood [73-76]. Marathon-induced changes in endocrine levels [77,78], in fluid balance [79] and amino acid blood level [80] are known to alter brain metabolism. The hypothesis that ultra endurance running leads to volume reduction of the brain cortex could be investigated by the TEFR project using high resolution cerebral MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Both aerobic and anaerobic exercise can induce a state of oxidative stress that leads to the physical reaction of an up-regulation in endogenous antioxidant defenses. 61 Gerlach et al 62 found support for the theory of S100B up-regulation under severe metabolic stress conditions such as hypoxia. They suggested that the secretion of S100B up to nanomolar concentrations is an early astroglial response to metabolic injury that initiates neuroprotective and neurotrophic effects.…”
Section: Categorization Of Sport-related S100b Reference Valuesmentioning
confidence: 97%
“…Mental and metabolic stress, as occurs in competitive sports, increases peripheral S100B levels in the absence of apparent brain injury. 59,[61][62][63][64] In an experimental study, Agawa et al 61 found serum serotonin levels increased during challenging exhaustive exercise. Teradaira et al 64 showed similar results by exposing sitting students to a stress model using visual display terminals; they noted increased plasma concentrations of serotonin.…”
Section: Categorization Of Sport-related S100b Reference Valuesmentioning
confidence: 99%
See 1 more Smart Citation